Kepatuhan Hukum Nasabah terhadap Kewajiban Pembayaran Angsuran Gadai - Mudini, Lulut; Sofiani, Trianah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Pawning is an activity of pledging valuables to a certain party in order to obtain a sum of money, with the agreement that the goods can be redeemed according to the agreement between the customer and the pawnshop. This study aims to analyze the level of customer legal compliance with the obligation to pay installments of pawn loans at Pegadaian Syariah, Batang Regency and to analyze the legal consequences of late payments. This study uses an empirical legal method with a qualitative approach. Data sources consist of primary and secondary data obtained through observation, interview, and documentation techniques, then analyzed descriptively. The results of the study indicate that the level of customer legal compliance in fulfilling installment payment obligations at PT Pegadaian Syariah, Batang Branch is still relatively low. This non-compliance is influenced by various factors, such as uncooperative attitudes, economic difficulties, and lack of understanding of pawn rules. Delays in installment payments give rise to various legal consequences, including the obligation to pay compensation, termination of the agreement, and sale of collateral through an auction mechanism.